Editorial - Van Patten, Elia María (1980)
Librarians who visit us are producing multiple documents, some of whom wish to share with our readers. Through them you will notice the emphasis that the Library Unit is giving school libraries in the country and the rest of Central America. With colleagues in the area are sharing the rich experiences in the Costa Rican Network of school libraries.